Modeling of a methanol synthesis process to utilize CO2 in the exhaust gas from an engine plant - Jeong, Jae Hun; Kim, Yoori; Oh, Se Young; Park, Myung June; Lee, Won Bo (Korean Journal of Chemical Engineering, 2022)
We investigated the conversion of CO2 in the exhaust gas of an engine plant into methanol. The process consists of CO2 purification by an acid gas removal unit (AGRU), mixed reforming, and methanol synthesis. The AGRU removes a large amount of inert gas, yielding CO2 of 98% purity at a recovery rate of 90% for use as feed to the reformer. The reformer temperature of 900 °C led to the almost total consumption of CH4. In the methanol synthesis reaction, the utility temperature had a greater influence on the conversion and methanol production rate than the inlet temperature. The optimal temperature was determined as 180 °C. Because the amount of hydrogen in the reformer effluent produced by dry reforming was insufficient, the steam available in the engine plant was used for mixed (dry and steam) reforming. The steam increased the hydrogen and methanol production rate; however, the compression cost was too high, and there exists an optimal amount of steam in the feed. The techno-economic analysis of the optimal conditions showed that utilization of CO2 in the exhaust gas along with freely available steam is economically feasible and reduces CO2 emissions by over 85%.
Keywords: CO2 Reduction; Engine Plant; Exhaust Gas; Methanol Synthesis; Techno-economic Analysis